2020
DOI: 10.3390/s20082360
|View full text |Cite
|
Sign up to set email alerts
|

A Double-Branch Surface Detection System for Armatures in Vibration Motors with Miniature Volume Based on ResNet-101 and FPN

Abstract: In this paper, a complete system based on computer vision and deep learning is proposed for surface inspection of the armatures in a vibration motor with miniature volume. A device for imaging and positioning was designed in order to obtain the images of the surface of the armatures. The images obtained by the device were divided into a training set and a test set. With continuous experimental exploration and improvement, the most efficient deep-network model was designed. The results show that the model leads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…In addition, we also compare the proposed method with other deep learning models, including Faster R‐CNN [39], YOLOv3 [40], Inception‐v3 [41], ResNet‐50, ResNet‐101 [42], Ref [26], and Ref [43]. Furthermore, the effectiveness of the mixed dataset augmentation and the ensemble learning proposed in this study is also demonstrated by ablative analysis.…”
Section: Experimental Dataset and Analysis Resultsmentioning
confidence: 95%
“…In addition, we also compare the proposed method with other deep learning models, including Faster R‐CNN [39], YOLOv3 [40], Inception‐v3 [41], ResNet‐50, ResNet‐101 [42], Ref [26], and Ref [43]. Furthermore, the effectiveness of the mixed dataset augmentation and the ensemble learning proposed in this study is also demonstrated by ablative analysis.…”
Section: Experimental Dataset and Analysis Resultsmentioning
confidence: 95%
“…The deep network has a low resolution and learns semantic features. The higher the level, the greater the abstraction of the features, the smaller the size of the feature map, and small-sized objects are easily missed ( 15 ). The location and size of the gallbladder in this study were different, and the deep residual convolutional network was relatively easy to false alarms, making the detection results inaccurate and affecting the classification accuracy of the model.…”
Section: Discussionmentioning
confidence: 99%
“…The ResNet has been widely applied to the field of natural language processes and computer vision 22,23 . To the best of our knowledge, we do not find any approaches that apply ResNet to code smell detection.…”
Section: Code Smell Detectionmentioning
confidence: 93%
“…The ResNet has been widely applied to the field of natural language processes and computer vision. 22,23 To the best of our knowledge, we do not find any approaches that apply ResNet to code smell detection. The traditional CNN model can not extract deep feature information of code metrics, resulting in relatively low accuracy.…”
Section: Improved Resnetmentioning
confidence: 99%